Jesus' cry from the cross : towards a first-century understanding of the intertextual relationship between Psalm 22 and the narrative of Mark's Gospel /: towards a first-century understanding of the intertextual relationship between Psalm 22 and the narrative of Mark's Gospel. (©2009) - Unknown
No abstract available